Should leader power and sex play an important role in predictiong influence tactics? - Lo, May-Chiun; Shazali, Abu Mansor; Ernest Cyril, de Run (International Journal of Management and Entrepreneurship, 2007)
Past researcher have indicated that an agent's power is a determinant of influence outcome on the targeted person. They explain on the relevance of power to organizational influence and leadership.